Epigenetic alterations in sepsis - Carrasqueiro, Gabriela Teixeira (2017)
Sepsis is a life-threatening complication of infection. Typically, a localized infection triggers a systemic inflammatory cascade resulting in widespread organ damage, organ failure, and often death. Of the 31.5 million cases of sepsis worldwide annually, it is estimated that there are 5.3 million deaths (Fleischmann et al., 2016). The pathophysiology of sepsis involves widespread reprogramming of gene expression. Bioinformatic approaches have revealed multiple gene pathways that are activated or inhibited in sepsis (DC Angus and Tom Van der Poll et al., 2013). Epigenetic mechanisms, including histone modifications, DNA methylation, and non-coding RNAs (such as microRNAs, siRNAs, andribosomal RNAs) are master regulators of gene expression in both normal and pathological states. Although there is limited data on epigenetic regulation of sepsis, localized epigenetic changes have been identified in individual genes.However no genome-wide data has yet been published. In this studywe define a number of sepsis-related DNA methylation changes in sepsis-associated genes. We correlate these changes with gene expression and with clinically-relevant outcomes. Finally, we will investigate the mechanisms by which DNA methylation regulates individual gene expression in sepsis.